Sebab Kematian Bayi Prematur Ditinjau dari Hasil Biopsi Post-Mortem Organ Tubuh - Soeripto, Soeripto (Universitas Gadjah Mada, 1985)
The mortality of the premature babies in Indonesia is still high. The exact cause of death is still unknown, because necropsy and pathological examination of the whole placenta are very rarely carried out. Needle biopsy of the dead premature babies organ is expected to help in searching the cause of death. A retrospective study was performed to reevaluate the biopsied organs of the dead prema tures from October 1970 through September 1971 in the Department of Pathology, Gadjah Mada University. Yogyakarta. The result of this study shows that early neonatal death of premature babies is 80,6% of all premature death. Based on histopathological examination of lung biopsies of those dead premature babies, it is clear that atelectasis is the primary cause, congestion the second, and Hyaline Membrane Disease (HMD) the third. Biopsies of other organs could not determine the exact cause of premature deaths as yet. Key Words: premature baby - early neonatal death - needle biopsy - atelectasis - Hyaline Membrane Disease